An indirect flow measurement based high-precision slide valve grinding mechanism for hydraulic servo valve. (1st January 2023) - Fan, Zeming; Fan, Jing; Yu, Xiaojun
Abstract: As a crucial power amplifying component for electro-hydraulic servo valves, the servo-valve spool valve largely determines the overall performance of an electro-hydraulic servo system. Due to the machining errors during the servo-valve manufacturing process, however, it is extremely difficult to characterize such response characteristics in engineering practice, and thus, there may exist certain nonlinearity between the flow rate and valve spool displacement caused by the spool and valve sleeve overlap. To accurately characterize the relationship between the flow rate and spool displacement to facilitate servo-valve production, an indirect flow measurement-based servo-valve spool valve grinding (FM-SVG) scheme is proposed in this study. Specifically, a valve spool overlap measurement mechanism is presented first based on the valve spool grinding principle, and then a data processing method is devised to eliminate the errors introduced by the fluctuations of differential pressure at the valve ports. Meanwhile, a closed-loop control system is also devised to maintain a constant differential pressure at the servo-valve ports. Finally, the FM-SVG scheme is embedded onto a lab-customized electro-hydraulic servo valve platform, and experiments are conducted to verify the feasibility and effectiveness of the FM-SVG scheme. Results show that, by utilizing the devised control scheme to maintain a differential pressure around 2.00 MP, the proposed grinding scheme helps achieve a grinding accuracy of 2.0 μm. With only grinding process needed, such a grinding scheme helps improve both grinding accuracy and production efficiency in practice.